فاعلية استراتيجية المماثلة ي التحصيل والتفكير الذكي في مادتي الرياضيات والجغرافية لدى طلبة الصف الرابع الأدبى - الكبيسي، عبدالواحد حميد ثامر; الكبيسي، ياسر عبدالواحد Alkubaisi, Yasser Abdulwahed (جامعة القدس المفتوحة, 2016)
The aim of this paper is to know the effectiveness of similar strategy in the achievement and smart thinking towards mathematics and geography at the fourth- grade students of literary stream. The sample consisted of 40 students who were divided into two groups equally, the first is the experimental for math and geography and the second is the control group. The first tool in the search measures the achievement test and the second measures the habits of mind. Appropriate statistical methods are used and their validity and reliability are tested. The results of the research are: 1. no statistically significant differences at the level (0.05) between the average achievement test scores posttest between the experimental group and the control group and the experimental group. 2. no statistically significant differences at the level (0.05) between the mean scores of the experimental group and the control group on the smart thinking and the experimental group scale.
هدف البحث إلى معرفة فاعلية استراتيجية المماثلة في التحصيل والتفكير الذكي لدى طلاب الصف الرابع الأدبي في مادتي الرياضيات والجغرافية، وتألفت عينة البحث من (40) طالباً توزعوا إلى مجموعتين بالتساوي، الأولى تجريبية درست باستراتيجية المماثلة (لمادتي الرياضيات والجغرافية) والضابطة بالطريقة التقليدية. واستخدم الباحثان أداتين في البحث الأولى اختبار تحصيلي، والثانية مقياس لعادات العقل وأجري لهما الصدق والثبات، واستخدمت الوسائل الإحصائية المناسبة وكان من نتائج البحث: 1. وجود فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسطي درجات الاختبار التحصيلي البعدي بين المجموعة التجريبية والمجموعة الضابطة، لصالح المجموعة التجريبية. 2. وجود فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسطي درجات المجموعة التجريبية والمجموعة الضابطة على مقياس التفكير الذكي لصالح المجموعة التجريبية.
Keywords: مقررات دراسية; طلبة الصف الرابع الأدبى; استراتيجية المماثلة; التحصيل الدراسى; تعليم; التفكير الذكي